Bringing the rain to Kapiti Plain : a Nandi tale - Aardema, Verna; Vidal, Beatriz (New York : Pied Piper, 1981)
A cumulative rhyme relating how Ki-pat brought rain to the drought-stricken Kapiti Plain.
"A Puffin Pied Piper.".
Child Study Children's Book Committee.
School Library Journal.
Wilson's Children.
3.4.
3.4
Keywords: Droughts -- Fiction; Stories in rhyme; Droughts -- Fiction; Stories in rhyme; Africa -- Fiction; Africa -- Fiction